Beam technologies for incineration and transmutation of the nuclear waste - Bomko, V.A.; Zajtzev, B.V.; Egorov, A.M. (Вопросы атомной науки и техники, 2001)
The problem of nuclear wastes is accounted from the viewpoint of 3 aspects: ecological expediency, influence on the environment, and safety with respect to explosion. The most efficient method is burning of the wastes in the Energy Amplifier, which is based on the complex of the reactor-accelerator. The goal of this paper is to scope the development of complex techniques of the transuranic elements (TRU) incineration, and transmutation most hazardous long-lived radionuclides, fragments of nuclear fission, eliminated with the heat removal through the natural convection of air. The main part of the work is associated with setting up the problem for Ukrainian nuclear energetics: the nuclear waste incineration as an alternative to the geological disposal.